الاشتراط في العقود وأثره في الأحوال الشخصية - فاطيمة بن جاب لله; رجاء حميدي; فاطمة عامر د/ (جامعة عمار ثليجي الاغواط, 2023)
تناولنا في هذا البحث الاشت ا رط المقترن بالعقود وأثاره على الأحوال الشخصیة حیت تناولنا في هذا الموضوع تعریف الشرط وأنواعه كما ذكرنا تعریف العقد وذكر قوامه وأقسامه وتطرقنا إلى مفهوم الشرط المقترن بالعقد والألفاظ ذات الصلة به وذكر الشروط الصحیحة والفاسدة ثم بینا مذاهب الفقهاء وأ ا رء العلماء في حكم الشروط المقترنة بالعقد مع ذكر الأدلة ومناقشاتها والترجیح في ثلاثة مسائل التي یمكن أن یشترطهما المتعاقدین, والتي من خلالها تحاول الم أ رة حمایة حقها في العمل والسكن المنفرد وعدم التعدد علیها. الكلمات المفتاحیة: الاشت ا رط - العقود - الأحوال الشخصیة - الشرط المقترن بالعقد. In this research, we dealt with the stipulation associated with contracts and its effects on personal status. In this topic, we dealt with the definition of the condition and its types. We also mentioned the definition of the contract and mentioned its strength and divisions. We also touched on the concept of the condition associated with the contract and related terms and mentioned the valid and corrupt conditions. Then we explained the doctrines of jurists and the opinions of scholars in the rule of associated conditions In the contract, mentioning the evidence and its discussions and weighting in three issues that may be stipulated by the contracting parties, and through which the woman tries to protect her right to work, to live alone, and not to have multiple wives. Keywords: stipulation - contracts - personal status - the conditio